One mechanism of spleen-kidney yang deficiency IBS-D: intestinal microbiota affect ATPase - Long, Qi; Li, Liwen; Deng, Na; Tan, Zhoujin (Frontiers in Microbiology, 2025)
BackgroundThis study aimed to investigate the effects of adenine and Folium senna combined with restraint tail-clamping stress method on the intestinal microbiota of mice with spleen-kidney yang deficiency type diarrhea predominant irritable bowel syndrome (IBS-D) from the perspective of energy metabolism.MethodsTwenty SPF-grade female mice were randomly divided into two groups, normal group (CN group) and model group (MD group), with 10 mice per group. A spleen-kidney yang deficiency IBS-D model was established using adenine and Folium senna combined with restraint tail-clamping stress. After model establishment, enzyme-linked immunosorbent assay (ELISA) was used to detect the activity of Na+-K+-ATPase and Ca2+-Mg2+-ATPase; spectrophotometry was used to measure intestinal digestive enzyme activity; fluorometric diacetate (FDA) hydrolysis spectrophotometry was used to detect intestinal microbial activity; and 16S rRNA sequencing was performed to identify intestinal microbiota in the intestinal contents.Results(1) ELISA showed a significant decrease in Na+-K+-ATPase and Ca2+-Mg2+-ATPase activity in spleen-kidney yang deficiency IBS-D model mice. (2) Intestinal enzyme activity analysis revealed increased lactase and amylase activity, and decreased sucrase activity in model mice. (3) Intestinal microbial activity analysis demonstrated significantly enhanced in microbial activity in spleen-kidney yang deficiency IBS-D model mice. (4) Correlation analysis revealed a significant positive correlation between Heminiphilus, Clostridium, Desulfovibrio and Ca2+-Mg2+-ATPase, a significant positive correlation between Heminiphilus and Na+-K+-ATPase, a significant positive correlation between Pediococcus and sucrase, and a significant negative correlation between Clostridium and sucrase.ConclusionReduced Na+-K+-ATPase and Ca2+-Mg2+-ATPase activities, increased sucrase and amylase activities, decreased lactase activity, and enhanced intestinal microbial activity may constitute important mechanisms underlying the development of spleen-kidney yang deficiency IBS-D.